RANCANGAN MODEL OPTIMASI LABA PRODUK SELSUN SHAMPOO MENGGUNAKAN METODE SIMPLEKS DI PT ABBORT INDONESIA - Hartono, Gunawarman; Lianawaty, Kiki (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
This study aims to find the optimal value of material planning for the company PT Abbott Indonesia. The purpose of this planning is to be able to obtain information efficiently and in terms of computation time and accuracy. Simplex method is a process that aims to find the optimal value is adjusted with a specific objective and a number of constraints. Using this method the result of this design is that with this optimization may yield a maximum profit. So that can help companies make decisions quickly and accurately about the amount of materials needed for each type of production that resulted. The value of the optimum solution is achieved at 4,386,950,750 with each variable X1 144.3651, X2 200, X3 106.6667, 107.2863 and X4